2014
DOI: 10.1590/s0004-28032014000300017
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF HELICOBACTER PYLORI ERADICATION ON HEPATIC STEATOSIS, NAFLD FIBROSIS SCORE AND HSENSI IN PATIENTS WITH NONALCOHOLIC STEATOHEPATITIS: a MR imaging-based pilot open-label study

Abstract: Context Limited clinical data suggest Helicobacter pylori (Hp) infection may contribute to nonalcoholic fatty liver disease (NAFLD) pathogenesis. Objectives The effect of Hp eradication on hepatic steatosis (magnetic resonance imaging), nonalcoholic fatty liver disease fibrosis score and HSENSI (Homocysteine, serum glutamic oxaloacetic transaminase, Erythrocyte sedimentation rate, nonalcoholic steatohepatitis Index) in nonalcoholic steatohepatitis patients. Methods Thirteen adult patients with biopsy-prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 27 publications
1
31
1
3
Order By: Relevance
“…The same authors also reported that patients with NAFLD had higher anti-H. pylori IgG titers, together with lower circulating adiponectin and higher tumor necrosis factor (TNF)-a levels (which all contribute to NAFLD pathogenesis), compared to non-NAFLD individuals [21]. Furthermore, still Polyzos et al [22] recently showed that, in a small group of patients with biopsy-proven nonalcoholic steatohepatitis, although H. pylori eradication had no long-term benefit on hepatic steatosis, a trend toward improvement was observed in the NAFLD fibrosis score and HSENSI (homocysteine, serum glutamic oxaloacetic transaminase, erythrocyte sedimentation rate, nonalcoholic steatohepatitis index), thereby warranting further relative investigation with larger studies using paired biopsies.…”
Section: Metabolic Syndromementioning
confidence: 95%
See 1 more Smart Citation
“…The same authors also reported that patients with NAFLD had higher anti-H. pylori IgG titers, together with lower circulating adiponectin and higher tumor necrosis factor (TNF)-a levels (which all contribute to NAFLD pathogenesis), compared to non-NAFLD individuals [21]. Furthermore, still Polyzos et al [22] recently showed that, in a small group of patients with biopsy-proven nonalcoholic steatohepatitis, although H. pylori eradication had no long-term benefit on hepatic steatosis, a trend toward improvement was observed in the NAFLD fibrosis score and HSENSI (homocysteine, serum glutamic oxaloacetic transaminase, erythrocyte sedimentation rate, nonalcoholic steatohepatitis index), thereby warranting further relative investigation with larger studies using paired biopsies.…”
Section: Metabolic Syndromementioning
confidence: 95%
“…Furthermore, still Polyzos et al. recently showed that, in a small group of patients with biopsy‐proven nonalcoholic steatohepatitis, although H. pylori eradication had no long‐term benefit on hepatic steatosis, a trend toward improvement was observed in the NAFLD fibrosis score and HSENSI (homocysteine, serum glutamic oxaloacetic transaminase, erythrocyte sedimentation rate, nonalcoholic steatohepatitis index), thereby warranting further relative investigation with larger studies using paired biopsies.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…It further supports the significance of H. pylori infection in the development of NAFLD. However, there were some studies declared that H. pylori infection is not related to NAFLD (Polyzos et al, 2014; Okushin et al, 2015; Baeg et al, 2016). In recent years, two studies from Korea and Japan involved 3,663 and 13,737 patients, respectively, found that H. pylori infection was not associated with NAFLD and may not be the risk factor for NAFLD (Okushin et al, 2015; Baeg et al, 2016).…”
Section: Epidemiology and Clinical Experimentsmentioning
confidence: 99%
“…Improved liver function tests (ALT and gamma‐glutamyl transferase [GGT]), hepatic steatosis (assessed with liver ultrasonography and the noninvasive fatty liver index [FLI]), and IR (assessed with HOMA‐IR) were reported in a man 2 months after successful eradication of H pylori ‐I . Likewise, we performed a pilot, 12‐month open‐label study evaluating the effect of H pylori eradication treatment on hepatic fat fraction (evaluated by magnetic resonance imaging) and noninvasive indices of fibrosis and NASH (NAFLD fibrosis score and homocysteine, serum AST, erythrocyte sedimentation rate, nonalcoholic steatohepatitis index [HSENSI], respectively) in biopsy‐proven NAFLD patient with H pylori ‐I, whereas noninfected NAFLD patients served as controls . We showed no effect of H pylori eradication on hepatic steatosis, but a trend toward improvement in noninvasive indices of fibrosis and NASH.…”
Section: Clinical Studies On the Association Between Helicobacter Pylmentioning
confidence: 99%